Ответ:
Пошаговое объяснение:
23*(x-12)=253
x - 12 = 253 : 23
x - 12 = 11
x = 11 + 12
x = 23
15*(2x+11)=285
2x + 11 = 285 : 15
2x + 11 = 19
2x = 19 - 11
2x = 8
x = 4
7*(123-4x)=749
123 - 4x = 107
4x = 123 - 107
4x = 16
23(х - 12) = 253
23х - 276 = 253
23х = 253 + 276
23х = 529
х = 529/23
х = 23
15(2х + 11) = 285
30х + 165 = 285
30х = 285 - 165
30х = 120
х = 120/30
х = 4
7(123 - 4х) = 749
861 - 28х = 749
-28х = 749 - 861
-28х = -112
х = -112/-28
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Ответ:
Пошаговое объяснение:
23*(x-12)=253
x - 12 = 253 : 23
x - 12 = 11
x = 11 + 12
x = 23
15*(2x+11)=285
2x + 11 = 285 : 15
2x + 11 = 19
2x = 19 - 11
2x = 8
x = 4
7*(123-4x)=749
123 - 4x = 107
4x = 123 - 107
4x = 16
x = 4
Verified answer
Ответ:
23(х - 12) = 253
23х - 276 = 253
23х = 253 + 276
23х = 529
х = 529/23
х = 23
15(2х + 11) = 285
30х + 165 = 285
30х = 285 - 165
30х = 120
х = 120/30
х = 4
7(123 - 4х) = 749
861 - 28х = 749
-28х = 749 - 861
-28х = -112
х = -112/-28
х = 4